Effects of interfacial interactions on structural, optical, thermal degradation properties and photocatalytic activity of low-density polyethylene/BaTiO3 nanocomposite. (16th May 2023) - Roy, Ayan; Panda, Sambit; Gupta, Jaya; Anu,; Singh, Ravi Pratap; Deeksha,; Kour, Pawanpreet; Sharma, M.P.; Yadav, Kamlesh
Abstract: Barium titanate ( BaTiO 3 ) filled low density polyethylene (LDPE), ( LDPE) 100−x / ( BaTiO 3 )x (where x = 0, 2, 4, 6 and 10) nanocomposites are prepared via a solvent-free melt-mixing method. The effects of nano-sized BaTiO 3 (nBT) on the structural, optical and thermal degradation properties of LDPE are investigated to address the qualitative interfacial interaction effects due to the spatial distribution of nBT particles in the LDPE matrix. X-ray diffraction (XRD) results confirm the uniform dispersion of nBT nano-fillers in the LDPE polymer matrix. The crystallite size of LDPE increases with increasing the nBT content. Fourier transform infrared spectroscopy (FTIR) results indicate the enhancement in interfacial physical interactions between the polymer and nano-fillers with increasing nano-filler content. The band gap energy of the nanocomposites decreases with increasing nano-filler content, which suggests chemical imperfections close to the interfaces. DSC results depict higher Tm values for the composites which is attributed to the heterogeneous nucleating effects of the nBT particles. Thermo-gravimetric analysis (TGA) results indicate an increase in the decomposition temperature ( T D ), thermal stability and good dispersibility probability of nBT with increasing nBT. The photocatalytic decomposition of MB is highest (73.52%) for the 10% nBT incorporated LDPE nanocomposite sample. These results correlate with the effect of the interfacial interactions between the nBT fillers and the LDPE polymer matrix. Graphical abstract: Image 1 Highlights: We have synthesized (LDPE)1-X /(BaTiO3 )X nanocomposites using melt-mixing method. Effects on thermal degradation properties with increasing nBT have been investigated. Band gap narrows after the incorporation of nBT in LDPE. Interfacial interactions and thermal stability increases, while exothermic degradation temperature (above 500 °C) decreases with increasing nBT loading. The photocatalytic decomposition of MB is highest (73.52%) for 10% nBT incorporated LDPE nanocomposite sample.